Bleaching and trophic ecology of corals on marginal reefs(Equatorial Southwestern Atlantic) - Lucas, Caroline Costa (2022)
Coral reefs are important ecosystems with high biodiversity and productivity in the tropical oceans. Besides that, offer services to society, such as coastal protection, maintenance of fish stocks, and scenic beauty that promotes tourism. The Equatorial Southwestern Atlantic region has a unique profile in terms of turbidity levels and high and stable seawater temperature, which is relevant for studies that assess the effect of environmental factors on reef communities such as scleractinians and zoantharians corals. Thus, this work was designed to understand the bleaching and trophic ecology of corals in the Equatorial Southwestern Atlantic using as a study model the reef ecosystems of the semiarid coast in northeastern Brazil. In Chapter I, we reported the bleaching of Siderastrea stellata and investigated the environmental factors that could have caused mass bleaching. It was observed that between February and June 2020, the reefs on the coast of Ceará State underwent two marine heatwaves (MHW) events in an interval of 8 days and with maximum intensity above the average temperature of approximately 1.9 °C and 1 .25°C. The degree heating week (DHW) during the bleaching period was 17.6 °C/week, the highest record in the last 17 years for the Equatorial Atlantic region. Therefore, we suggest that these factors, together with low turbidity and wind speeds, may have caused the bleaching together with meteorological variables. In chapter II we analyze the bleaching, along 3 years (2013-2015), of tolerant specie S. stellata and the relationship with the climatic and oceanographic conditions of the period. We found that there was a deficit in rainfall between 2013 and 2015. The low rainfall of the period may have reduced cloudiness and turbidity, which left the coral colonies in shallow-water unprotected against solar radiation and occasioned bleaching in certain periods of the year. In the third and last chapter, the trophic ecology of zoanthid corals Palythoa caribaeorum, Palythoa variabilis, and Zoanthus sociatus was addressed through an integrative review. Z. sociatus is an autotrophic species and seems to have an affinity for particulate organic matter as an external food source. P. caribaeorum and P. variabilis seem to use more of the heterotrophic pathway. P. caribaeorum seems to have a preference for phytoplankton in its diet. The different trophic strategies help to explain its abundance, resistance, and wide distribution in reef communities in the Equatorial Atlantic. Reef communities in the Equatorial Southwestern Atlantic and their responses to environmental factors may provide new and intriguing answers to help understand coral resistance to global environmental changes.